2021
DOI: 10.12659/msm.929435
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA MEG3 Downregulation Relieves Intracerebral Hemorrhage by Inhibiting Oxidative Stress and Inflammation in an miR-181b-Dependent Manner

Abstract: Background This study was designed to illustrate the effects and latent mechanism of lncRNA maternally expressed gene 3 (MEG3) on intracerebral hemorrhage (ICH)-induced brain injury. Material/Methods An ICH rat model was generated to determine the role of lncRNA MEG3 in ICH. The interaction between lncRNA MEG3 and microRNA (miR)-181b were confirmed by Starbase and dual-luciferase reporter assay. One hour (h) or 3 days after ICH stimulation, rat neurological injury was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…Similarly, MEG3 is up-regulated in the brain tissue of intracerebral hemorrhage (ICH) rats. Abating MEG3 expression restrains edema, neuronal apoptosis, and the release of inflammatory cytokines and oxidative stress in the brain tissue of ICH rats [ 18 ]. Therefore, MEG3 can play a role in neuroinflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, MEG3 is up-regulated in the brain tissue of intracerebral hemorrhage (ICH) rats. Abating MEG3 expression restrains edema, neuronal apoptosis, and the release of inflammatory cytokines and oxidative stress in the brain tissue of ICH rats [ 18 ]. Therefore, MEG3 can play a role in neuroinflammation.…”
Section: Introductionmentioning
confidence: 99%
“…MEG3 has been identified as a tumor inhibitor and can also promote inflammation, oxidative stress, and cell apoptosis of non-tumor cells in previous studies [ 12 , 16 , 17 ]. As shown in Figure 2(a) , the MEG3 expression was significantly elevated by TNF-α treatment in ICC ( p < 0.05), which suggested that MEG3 might be involved in the stress process of ICC with TNF-α stimulation.…”
Section: Resultsmentioning
confidence: 99%
“…Many previous studies have demonstrated that MEG3 participates in the inflammation progression and apoptosis in different types of non-cancer cell [ 15 , 50 , 51 ]. A study by Xie B et al suggested that MEG3 downregulation suppresses the inflammation cytokines and oxidative stress level [ 17 ]. In agreement with these reporters, our study verified MEG3 was upregulated by TNF-α in ICC, and knockdown of MEG3 reduced inflammation, oxidative stress, and apoptosis in TNF-α-treated ICC.…”
Section: Discussionmentioning
confidence: 99%
“…129,134,135 In an ICH rat model, MEG3 downregulation reduced caspase-3 activity and apoptosis, and ameliorated inflammation and oxidative stress. 136 Expression of MEG3 was increased in the cerebrospinal fluid of SAH patients, and in the blood of ischemic stroke patients, which was associated with the severity of post-stroke brain damage. 137,138 These clinical studies further indicate that MEG3 may be involved in exacerbation of brain injury after stroke.…”
Section: Long Noncoding Rnas As Epigenetic Regulators In Strokementioning
confidence: 98%